Chloroplast pigments, water relationships, and growth of bell pepper under salt stress and nitrogen - Roque, Iara Almeida; Soares, Lauriane Almeida dos Anjos; Lima, Geovani Soares de; Lopes, Iracy Amelia Pereira; Silva, Luderlândio de Andrade; Dantas, Maíla Vieira; Torres, Rafaela Aparecida Frazão; Souza, Weslley Bruno Belo de (Comunicata Scientiae, 2024)
The use of saline water sources for irrigation in semi-arid regions is a challenge for horticultural production since plants are sensitive to salt stress conditions, thus requiring techniques that allow plant acclimation, including nitrogen fertilization. From this perspective, this study aimed to evaluate the chloroplast pigments, water relationships, and growth of bell pepper plants irrigated with saline water and subjected to nitrogen fertilization. The experiment was conducted under field conditions at the Federal University of Campina Grande, Pombal - PB, where a randomized block design was adopted with a 5 x 5 factorial arrangement corresponding to five electrical conductivity levels of irrigation water (0.3, 1, 1.7, 2.4, and 3.1 dS m-1) and five nitrogen levels (50, 75, 100,125, and 150% of the dosage recommended for the crop), with three replications. The 125 and 150% N levels provided the highest relative water contents in bell pepper plants irrigated with electrical conductivity levels of up to 1.7 dS m-1. The contents of chlorophyll a, b, total chlorophyll, carotenoids, and stem diameter of bell pepper plants decreased when fertilized with 150% N and irrigated with the electrical conductivity of 3.1 dS m-1.